Safety, beneficial and technological properties of enterococci for use in functional food applications – a review. Issue 22 (15th December 2020) - Graham, Ken; Stack, Helena; Rea, Rosemary
Abstract: Enterococci are ubiquitous lactic acid bacteria (LAB) that predominantly reside in the gastrointestinal tract of humans and animals but are also widespread in food and the environment due to their robust nature. Enterococci have the paradoxical position of providing several benefits of technological interest in food fermentations but are also considered as opportunistic pathogens capable of causing infection in immunocompromised patients. Several species of the genus have been correlated with disease development in humans such as bacteremia, urinary tract infections, and endocarditis. The pathogenesis of enterococci has been attributed to the increasing incidence of antibiotic resistance and the possession of virulence determinants. On the contrary, enterococci have led to improvements in the aroma, texture, and flavor of fermented dairy products, while their beneficial use as probiotic and protective cultures has also been documented. Furthermore, they have emerged as important candidates for the generation of bioactive peptides, particularly from milk, which provide new opportunities for the development of functional foods and nutraceuticals for human nutrition and health. The detection of pathogenic traits among some species is compromising their use in food applications and subsequently, the genus neither has Generally Regarded as Safe (GRAS) status nor has it been included in the Qualified Presumption of Safety (QPS) list. Nevertheless, the use of certain enterococcal strains in food has been permitted on the basis of a case-by-case assessment. Promisingly, enterococcal virulence factors appear strain specific and food isolates harbor fewer determinants than clinical isolates, while they also remain largely susceptible to clinically relevant antibiotics and thus, have a lower potential for pathogenicity. Ideally, strains considered for use in foods should not possess any virulence determinants and should be susceptible to clinically relevant antibiotics. Implementation of an appropriate risk/benefit analysis, establishment of a strain's innocuity, and consideration for relevant guidelines, legislation, and regulatory aspects surrounding functional food development, may help industry, health-staff and consumers accept enterococci, like other LAB, as important candidates for useful and beneficial applications in food biotechnology.